UTILIZATION OF SOCIAL COHESION THROUGH MULTICULTURAL COUNSELING IN RESOLVING SOCIAL CONFLICTS (STUDENT FIGHTS) - Yenni Elfira; Firman; Riska Ahmad (Literasi Nusantara, 2021)
The research was conducted using a systematic literature study approach on various literatures regarding the use of social cohesion through multicultural counseling in the resolution of social conflicts (brawls between students). Brawls between students are considered a trend for some students to show strength, even if it is only caused by personal or trivial problems. This is motivated by the low understanding of students about diversity and togetherness. Therefore, multicultural counseling services are one way that can be done so that students can live together in a multicultural society and can foster cultural awareness and create closer social cohesion between students. So as to avoid teenage social conflicts or brawls between students.